Legal Protection for Communities in Infrastructure Development Based on State Administrative Law: Perlindungan Hukum Masyarakat dalam Pembangunan Infrastruktur berdasarkan Hukum Administrasi Negara - Nabila Dwi Arneta; Kurniati Dwi Putri; Sinta Aulianti (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Infrastructure development is central to national progress, yet it often generates displacement, environmental degradation, and social tension for communities near project areas. Specific Background: Although Indonesia possesses legal frameworks governing land acquisition and administrative procedures, affected communities frequently face limited transparency, insufficient participation, and restricted access to administrative remedies. Knowledge Gap: Prior studies predominantly emphasize agrarian and civil law, leaving the role of State Administrative Law in community legal protection insufficiently examined. Aims: This study explores how State Administrative Law provides legal protection for communities during infrastructure development through administrative instruments, procedures, and dispute-resolution mechanisms. Results: Findings reveal that administrative safeguards remain weak due to inconsistent application of administrative procedures, inadequate oversight, and ineffective preventive mechanisms, often pushing communities to rely on administrative litigation such as PTUN. Novelty: The study offers a four-pillar framework consisting of regulatory strengthening, professional and transparent bureaucracy, reinforced preventive and repressive administrative enforcement, and community empowerment through participatory access to justice. Implications: Strengthening administrative law mechanisms is essential to ensure that infrastructure development aligns with good governance principles and guarantees fair, accountable, and accessible legal protection for affected communities. Highlights: Administrative law serves as a key foundation for ensuring community legal protection in infrastructure development. Limited transparency and weak oversight hinder the enforcement of community rights. Strengthened administrative mechanisms are necessary to uphold fairness and accountability in development processes. Keywords State Administrative Law, Legal Protection, Infrastructure Development, Public Participation, Governance Compliance